Consolidation of Fe-Based Metallic Glass Powders by Hot Pressing - Santana,Diego de Araujo (2019)
An alternative route to obtain bulk metallic glasses is by consolidation of metallic glass powders by deforming these materials in the temperature interval between the crystallization temperature and the glass transition temperature, where the material flows with a reduced viscosity. In the present work, bulk parts of the Fe43.2Co28.8B19.2Si4.8Nb4 alloy were produced by hot-pressing gas-atomized powders (GAP) under different uniaxial pressures. Different microstructural analysis revealed that the initial powder as well as the consolidated parts were mostly amorphous, with similar transformation temperatures, showing that bulk samples of this alloy can be produced by conformation in the supercooled liquid region. The sample conformed under the highest pressure (1GPa) exhibited the highest relative density of 96.1±0.5%. These results show that hot pressing of Fe-based gas-atomized powders is a promising route for producing Fe-based bulk metallic glasses.